PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Terdaftar Di LQ45 Tahun 2020-2022) - Pranita, Fera Lufhidarani (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to analyze the effect of inflation, interest rates and exchange rates on stock prices. Case studies of companies listed on LQ45 in 2020-2022. This study uses a quantitative approach method. The research sample used is 27 companies listed on LQ45 within three years from 2020-2022. Quantitative data used are data on inflation, interest rates, exchange rates and LQ45 stock prices. The analysis technique used is multiple linear regression. Hypothesis testing uses the t test (partial test) and F test (simultaneous test). The results of the study show that partially Inflation and Exchange Rates have an effect on the share prices of companies listed on LQ45 in 2020-2022, while simultaneously showing that Inflation, Interest Rates and Exchange Rates have a significant effect on Share Prices of companies listed on LQ45 in 2020-2022.Keywords: Inflation, Interest Rates, Exchange Rates, Stock Prices